2004
DOI: 10.1596/1813-9450-3400
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Infrastructure Development on Growth and Income Distribution

Abstract: This paper provides an empirical evaluation of the impact of infrastructure development on economic growth and income distribution using a large panel data set encompassing over 100 countries and spanning the years 1960-2000. The empirical strategy involves the estimation of simple equations for GDP growth and conventional inequality measures, augmented to include among the regressors infrastructure quantity and quality indicators in addition to standard controls. To account for the potential endogeneity of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
517
2
26

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 590 publications
(562 citation statements)
references
References 53 publications
17
517
2
26
Order By: Relevance
“…This is fundamentally because high inflation creates uncertainty due to growing ambiguity and investors have been documented to prefer less ambiguous economic strategies (Le Roux & Kelsey, 2016ab). On the positive indicators, they have been substantially documented in the bulk of inclusive growth literature (Dollar & Kraay, 2003;Barro & Lee, 2000;Calderon & Servén, 2004;Levine, 2005;Hausmann et al, 2007;IMF, 2007;Mishra, et al, 2011;Anand et al, 2012;Seneviratne & Sun, 2013;Asongu & Nwachukwu, 2016ab).…”
Section: Datamentioning
confidence: 98%
See 1 more Smart Citation
“…This is fundamentally because high inflation creates uncertainty due to growing ambiguity and investors have been documented to prefer less ambiguous economic strategies (Le Roux & Kelsey, 2016ab). On the positive indicators, they have been substantially documented in the bulk of inclusive growth literature (Dollar & Kraay, 2003;Barro & Lee, 2000;Calderon & Servén, 2004;Levine, 2005;Hausmann et al, 2007;IMF, 2007;Mishra, et al, 2011;Anand et al, 2012;Seneviratne & Sun, 2013;Asongu & Nwachukwu, 2016ab).…”
Section: Datamentioning
confidence: 98%
“…While structural change entails globalisation (FDI and trade), human capital and macroeconomic stability embody, inter alia: educational levels, technological change and fixed investment. Other structural and macroeconomic features essential for the growth process are inflation and 8 output volatility (Dollar & Kraay, 2003;Barro & Lee, 2010), finance (Levine, 2005); infrastructural development (Calderon & Servén, 2004;Seneviratne & Sun, 2013); development of value chains (Hausmann et al, 2007;Anand, et al, 2012) and production modernization (Mishra et al, 2011). The summary statistics are presented in Appendix 2 whereas the correlation matrix is in Appendix 3.…”
Section: Datamentioning
confidence: 99%
“…In fact, Calderón and Servén (2005) presented an empirical analysis focusing on Latin America. They reported positive and significant output contributions of three types of infrastructure assets, i.e., telecommunications, transport and power.…”
Section: Relationship Between Infrastructure and Growthmentioning
confidence: 99%
“…With regard to infrastructure and income inequality, they concluded that availability and quality of infrastructure services for the poor in developing countries had a significant positive impact on their health and/or education and, hence, on income and welfare. Calderón and Servén (2005) also dealt with the issue of private participation in infrastructure investment by examining how large an increase, if any, there was in its pro-poor effect. They considered the important aspect of distributive impact of private participation in infrastructure, which had attracted considerable attention and which involved both macro and microeconomic linkages.…”
Section: (A)mentioning
confidence: 99%
“…For example, Calderón and Chong (2004), Calderón and Servén (2004), Fan and Zhang (2004), Ferranti et al (2004), and Lopez (2004) find that public investment has both promoted growth and helped mitigate inequality. 2 On the other hand, Brakman et al (2002) find that government spending on infrastructure has increased regional disparities within Europe, while Artadi and Sala-i-Martin (2003) suggest excessive public investment has contributed to rising income inequality in Africa.…”
Section: Introductionmentioning
confidence: 99%